Supplementary Activities of The Capital Market School to Nurture The Spirit of Investment Consciousness - Nitawati, Elly Yuniar; Iman, Nurul; Sa’adah, Ummi; Putra, Briyan Cadalora (Jurnal Pengabdian Masyarakat Bestari, 2024)
Investment is the activity of putting a quantity of capital (money or other valuable assets) into an object, institution, or party with the hope that after a certain period of time it will make a profit. The term "investment" is becoming more and more common amongst society given the increasing number of products produced. With the increasing number of investment products, investing is becoming very complex especially for public investors who have not really understood the intricacies of investing. This capital market school activity lasted for one day. Some of the materials that will be introduced concern general knowledge of investment and capital markets provided by experts in their field. The expected outcome of this capital market activity is that students as participants of the Capital Market school activities, can understand the activities that take place in the Capital market easily through the delivery of materials, discussions, or through practice in person. After the implementation of the activities of this Capital Market School, then the participants  can gain several benefits which can be used to make transactions in the capital market.